Impact of introducing a lactation consultant into a neonatal unit. (29th October 2021) - Broom, Margaret; Youseman, Mary‐Ellen; Kent, Alison L
Abstract : Aim: Benefits of mothers' own milk (MOM) for premature and sick neonates are well documented. To increase access, many neonatal units have a lactation consultant (LC) on staff. This study aimed to assess the impact of a permanent LC on (i) maternal access to LC support; (ii) staff confidence in providing Breast Feeding (BF) education and (iii) provision of MOM. Methods: Study included a staff survey and chart audit. Questions provided feedback on access to lactation support and meeting maternal needs. Audit data included: gestational age, birthweight, intention to breastfeed, documentation of LC appointment, provision of MOM at 12 hours, days 3, 7, 28 and discharge. Student's t ‐tests were used for numerical data and chi‐squared tests for categorical variables. Results: Ninety‐one staff surveys were returned, (pre 35/75 (47%), post 56/85 (66%) with staff reporting organising an LC appointment was significantly easier ( P  < 0.0001). Staff perceived maternal lactation needs and confidence to breastfeed post‐discharge had significantly improved post‐LC. The chart audit showed a significant increase in maternal access to LC appointments (15% vs. 80%; P  < 0.01), breast pump education by day 3 (65% vs. 81%; P  < 0.01), and an increase in MOM provision by 12 h (46% vs. 61%; P  < 0.01) post‐LC but not at days 7, 28 or discharge. Conclusion: A dedicated LC increases staff and maternal access to lactation education and support, improving provision of early MOM. Further research is required to assess the effect of LCs in improving breastfeeding rates in neonatal units.